2010
DOI: 10.1590/s1679-78252010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic instability of imperfect laminated sandwich plates with in-plane partial edge load

Abstract: Dynamic instability of laminated sandwich plates having inter-laminar imperfections with in-plane partial edge loading is studied for the first time using an efficient finite element plate model. The plate model is based on a refined higher order shear deformation plate theory, where the transverse shear stresses are continuous at the layer interfaces with stress free conditions at plate top and bottom surfaces. A linear spring-layer model is used to model the inter-laminar imperfection by considering in-plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Equation (7) is the eigen-value problem that gives the desired loading frequency value W ¼ w=2 in the forms of upper W U À Á and lower W L À Á stability boundaries of the dynamic instability region for known values of a, b and P cr . Finite element method source codes have been developed in FORTRAN environment to solve equation (7).…”
Section: The Finite Element Methods Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (7) is the eigen-value problem that gives the desired loading frequency value W ¼ w=2 in the forms of upper W U À Á and lower W L À Á stability boundaries of the dynamic instability region for known values of a, b and P cr . Finite element method source codes have been developed in FORTRAN environment to solve equation (7).…”
Section: The Finite Element Methods Formulationmentioning
confidence: 99%
“…A study showed that the dynamic instability region of laminated composite plates that were subjected to wide ranges of combined static and harmonically varying in-plane point and patch loads can be increased with the increase in the load bandwidths [6]. Dynamic instability of parts of turbines, electric machines and parts of aircraft or ships were studied by modelling them as laminated sandwich plates while the refined higher order theory was used in the formulation [7]. Later, the inverse trigonometric hyperbolic zig-zag theory was used to investigate the parametric instability of laminated composite and sandwich plates [8].…”
Section: Introductionmentioning
confidence: 99%
“…118 It was found that no solution exists in the literature for the problem of sandwich plate subjected to partial edge loading and investigated by a newly developed triangular element based on an RHSDT, where the continuity of stresses is satisfied at the layer interfaces by taking jumps in the transverse shear strains at the interfaces. It is interesting to note that the plate model having all these refined features requires unknowns at the reference plane only, [119][120][121][122] and the different degrees of imperfections at the layer interfaces were investigated. 123 An FE analysis is carried out using commercial ABAQUS software, version 6.14.…”
Section: Figure 1 Geometry and Coordinates Of A Sandwich Platementioning
confidence: 99%
“…The effect of span to thickness ratio, modular ratio, boundary conditions, static load factor, and thickness ratios were examined by solving a variety of numerical problems on laminated composite and sandwich structures. Dynamic instability behavior of composite and sandwich laminates with interfacial slips was studied by Chakrabarti and Sheikh [12] by using the refined higher order shear deformation theory and later the same theory combining with linear spring model was used to study the dynamic instability of imperfect laminated sandwich plates having in-plane partial edge loading. This paper reports on the dynamic instability study conducted on symmetric angle-ply composite plate.…”
Section: Introductionmentioning
confidence: 99%